2010
DOI: 10.5209/rev_jige.2010.v36.n2.11
|View full text |Cite
|
Sign up to set email alerts
|

Choristoderes and the freshwater assemblages of Laurasia

Abstract: Choristoderes are freshwater aquatic diapsid reptiles of uncertain phylogenetic position. Although the lineage probably diverged from other diapsids in the Permo-Triassic, choristoderes apparently never reached Gondwana. Within Laurasia, however, they have been recovered from Japan, China, Mongolia, Trans-Baikal Russia, Central Asia, Western Europe, and North America, reaching extreme northern latitudes. Setting aside controversial Triassic records, their known temporal range currently extends from the Middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 58 publications
2
68
0
Order By: Relevance
“…Pachystropheus was the only known choristodere not found in freshwater deposits. However, this identification has been queried: Matsumoto and Evans (2010) noted that the diagnostic characters of choristoderes are in the skull, and yet only one cranial bone of P. rhaeticus has been found. Renesto (2005) suggested that Pachystropheus might be related to Endennasaurus from the Late Triassic of Italy, a possible thalattosaur, based on the common occurrence of 22 characters regarded by Storrs and Gower (1993) as unique to choristoderes; thalattosaurs are marine.…”
Section: Pachystropheus Was Initially Described On the Basis Of Fragmmentioning
confidence: 99%
“…Pachystropheus was the only known choristodere not found in freshwater deposits. However, this identification has been queried: Matsumoto and Evans (2010) noted that the diagnostic characters of choristoderes are in the skull, and yet only one cranial bone of P. rhaeticus has been found. Renesto (2005) suggested that Pachystropheus might be related to Endennasaurus from the Late Triassic of Italy, a possible thalattosaur, based on the common occurrence of 22 characters regarded by Storrs and Gower (1993) as unique to choristoderes; thalattosaurs are marine.…”
Section: Pachystropheus Was Initially Described On the Basis Of Fragmmentioning
confidence: 99%
“…Storrs and Gower (1993) assigned it to Choristodera, a group of crocodile-like semi-aquatic diapsids, found in freshwater habitats. However, this is problematic because the skull contains the diagnostic features of choristoderes (Matsumoto and Evans, 2010), but only one cranial bone has been found of P. raeticus. Renesto (2005) suggested that Pachystropheus might be related to Endennasaurus from the Late Triassic of Italy, a possible thalattosaur, based on the common occurrence of 22 characters regarded by Storrs and Gower (1993) as unique to choristoderes.…”
mentioning
confidence: 99%
“…The timing of the radiation of the non-neochoristodere group, Monjurosuchidae, is a point of ongoing study, although their origin might be in the Early Cretaceous of Asia (Gao & Fox, 2005;Averianov et al, 2006;Richter et al, 2010;Gao et al, 2013). The earliest records of the major lineage Neochoristodera occur in Barremian (Early Cretaceous) deposits of Asia (Matsumoto & Evans, 2010) and North America (Britt et al, 2006), and this lineage persisted well past the K/Pg boundary (Evans & Klembara, 2005). There appears to have been an ecological transition around the J/K boundary, from smaller basal forms (Late Jurassic), to larger taxa, primarily representing neochoristoderes (Early Cretaceous onwards), with non-neochoristoderes seemingly becoming extinct in Euamerica (Matsumoto & Evans, 2010).…”
Section: (G) Choristoderesmentioning
confidence: 99%